Analisis Pertumbuhan Sepeda Listrik dan Upaya Pencegahan Kecelakaan Lalu Lintas di Indonesia - Amanda Cahya Pratama; Aurelia Hermawan; Pitria Ramadhanie (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This research analyzes the growth of electric bicycles and efforts to prevent traffic accidents in Indonesia. The method used is a literature study to collect and analyze data from various sources. The results show that stricter regulations, supportive infrastructure development, and traffic safety education are needed to reduce the risk of accidents. Consistent law enforcement is also key in reducing the number of accidents involving electric bicycles. With these steps, it is hoped that a safer driving environment can be created for electric bicycle users in Indonesia.